Sejarah Manajemen Pendidikan Era Klasik : Plato, Confucius, Al-Farabi - Asiyah Asiyah; Ermi Aprilia; Hilman Nugraha; Afindi Afindi; Hendri Dunan (Lembaga Pengembangan Kinerja Dosen, 2025)
The classical era presented many great figures who made important contributions to the philosophy of education and its management. Among the most influential figures are Plato from Greece, Confucius from China, and Al-Farabi from the Islamic world. The purpose of this study is to describe and analyze the history of educational management in the Classical era: Plato, Confucius, Al-Farabi. Using the Library Research method. The results of the study show that education has been seen from the beginning as an important means in forming a complete human being. Plato, Confucius, and Al-Farabi as great figures from Greece, China, and the Islamic world made fundamental contributions to the concept of education that emphasizes the development of reason, morals, and spirituality. Their thoughts were born from different cultural backgrounds and civilizations, but had the same goal, namely to form people with character, knowledge, and contribute to society and the state. This shows that classical education is not just a transfer of knowledge, but also a means of forming individuals and civilization.